THE INFLUENCE OF BUSINESS RISK TOWARD CAPITAL ADEQUACY RATIO (CAR) ON FOREIGN EXCHANGE NATIONAL PRIVATE COMMERCIAL GO PUBLIC BANKS - Gustaf Naufan Febrianto; Anggraeni Anggraeni (Journal of Business & Banking, 2016)
The purpose of the research is to determine LDR, IPR, NPL, APB, IRR, PDN, FBIR, and BOPO simultaneously and partially have significant influence toward Capital Adequacy Ratio (CAR).Population were the foreign Exchange National Private Commercial Go Public Banks. Sampling technique is purposive sampling so that the selected Bank were Himpunan Saudara 1906, Ekonomi Raharja and bank Mayapada International. Data collected by the methods of documentation and analysis were performed by linear multiple regression analysis technique.Results shows that LDR, IPR, NPL, APB, IRR, PDN, FBIR And BOPO simultaneously have significant effect toward Capital Adequacy Ratio (CAR) ratio on foreign Exchange National Private Commercial Go Public Banks. Partially BOPO ratio significantly has a negative effect on Capital Adequacy Ratio (CAR) ratio. Meanwhile LDR, IPR, NPL, IRR and FBIR has a possitive effect but insignificant toward CAR ratio On foreign Exchange National Private Commercial Go Public Banks. On the other side APB and PDN have negative effect but insignificant toward CAR ratio on foreign Exchange National Private Commercial Go Public Banks.